Gene-regulatory activity of alpha-tocopherol. - Rimbach, G.; Moehring, J.; Huebbe, P.; Lodge, John K. (MDPI, 2010)
Vitamin E is an essential vitamin and a lipid soluble antioxidant, at least, under in vitro conditions. The antioxidant properties of vitamin E are exerted through its phenolic hydroxyl group, which donates hydrogen to peroxyl radicals, resulting in the formation of stable lipid species. Beside an antioxidant role, important cell signalling properties of vitamin E have been described. By using gene chip technology we have identified alpha-tocopherol sensitive molecular targets in vivo including christmas factor (involved in the blood coagulation) and 5alpha-steroid reductase type 1 (catalyzes the conversion of testosterone to 5alpha-dihydrotestosterone) being upregulated and gamma-glutamyl-cysteinyl synthetase (the rate limiting enzyme in GSH synthesis) being downregulated due to alpha-tocopherol deficiency. Alpha-tocopherol regulates signal transduction cascades not only at the mRNA but also at the miRNA level since miRNA 122a (involved in lipid metabolism) and miRNA 125b (involved in inflammation) are downregulated by alpha-tocopherol. Genetic polymorphisms may determine the biological and gene-regulatory activity of alpha-tocopherol. In this context we have recently shown that genes encoding for proteins involved in peripheral alpha-tocopherol transport and degradation are significantly affected by the apoE genotype.